DEVELOPING SOCIAL AND SERVICE SECTORS THROUGH DIGITALIZATION OF COMMERCIAL BANKS IN A MODERN ECONOMY - Norqulov Habibullo; Zubaydulloyeva Damira; Suyunov Azizjon (European Science Publishing, 2025)
This article examines the prospects for the introduction of digital services in commercial banks in the modern economy, scientific views aimed at studying the ways to successfully implement digital technologies, improve customer service and increase the overall efficiency of banks. In today's digital economy, the introduction of digital services for banks serves not only as a convenience, but also as an important factor ensuring competitiveness.
Keywords: Commercial banks, digital services, digitization, banking services, financial services, remote service.